1999
DOI: 10.1002/(sici)1097-0290(19990920)64:6<741::aid-bit14>3.3.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic analysis of chimeric antibody‐producing CHO cells in the course of dihydrofolate reductase‐mediated gene amplification and their stability in the absence of selective pressure

Abstract: Previously, the highest producing (HP) recombinant CHO subclones isolated at various methotrexate (MTX) levels showed different antibody production stability during long-term culture, although they were clonally derived from CS13 transformant. In this study, genetic basis for their difference in antibody production stability was investigated using southern blot hybridization and fluorescence in situ hybridization (FISH) techniques. Southern analysis of HP subclones revealed that light-chain (LC) and heavy-chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The antibody titer reached in a four-day shake flask culture declined by only 31% over 36 passages without MTX for the more stable clone M500-11, whereas it decreased by 92% for the less stable clone M500-2. These findings are consistent with previous reports showing that dhfr-mediated gene-amplified CHO cells are not only very heterogeneous in regard to transgene copy numbers, mRNA levels, and productivity, but also in regard to production stability, despite being derived from a single parent clone (Fann et al, 2000;Hammill et al, 2000;Kim and Lee, 1999;Kim et al, 1998a,b;Pallavicini et al, 1990;Sinacore et al, 1994;Weidle et al, 1988;Yoshikawa et al, 2000a,b). Several studies reported that production stabilized after an initial 60-70% decrease in productivity upon removal of MTX selection pressure (Fann et al, 2000;Weidle et al, 1988).…”
Section: Clone Stability Studiessupporting
confidence: 92%
“…The antibody titer reached in a four-day shake flask culture declined by only 31% over 36 passages without MTX for the more stable clone M500-11, whereas it decreased by 92% for the less stable clone M500-2. These findings are consistent with previous reports showing that dhfr-mediated gene-amplified CHO cells are not only very heterogeneous in regard to transgene copy numbers, mRNA levels, and productivity, but also in regard to production stability, despite being derived from a single parent clone (Fann et al, 2000;Hammill et al, 2000;Kim and Lee, 1999;Kim et al, 1998a,b;Pallavicini et al, 1990;Sinacore et al, 1994;Weidle et al, 1988;Yoshikawa et al, 2000a,b). Several studies reported that production stabilized after an initial 60-70% decrease in productivity upon removal of MTX selection pressure (Fann et al, 2000;Weidle et al, 1988).…”
Section: Clone Stability Studiessupporting
confidence: 92%
“…1g) was the only clone that exhibited a signal on the short arm of an acrocentric chromosome. Analysis of the integration site of the cotransfected dhfr gene (as expression vectors with different backbones have been used for transfection, no unspecific signal could be obtained) revealed co-localisation to the integration site of the target gene (pictures not shown), which is reported in several studies (Pallavicini et al 1990;Chen et al 1998;Strutzenberger et al 1999;Kim et al 1999). Analysis of the chromosome number (at least 20 metaphase preparations were counted) of the EpoFc clone family revealed an average diploid chromosome number of 20 chromosomes for clones 2C10, 2G4 and 2G6.…”
Section: Analysis Of the Epofc Clone Familymentioning
confidence: 99%
“…An efficient combination of selection, screening and gene amplification leads to stably and highly producing clones ready to be propagated in scalable reactors. Various studies (Davies et al 2001;Kaufman et al 1983;Kim et al 1999;Pallavicini et al 1990;Yoshikawa et al 2000a, b;Derouazi et al 2006) have investigated the influence of the integration locus on stability and productivity of the clones in order to obtain an additional criterion for clone selection since the majority of random integration sites leads to low level expression (Barnett et al 1995). Furthermore, information of insertion loci which allow gene amplification and support high productivity and stability-in addition with systems for site-directed integration (the Flp/FRT system from the yeast Saccharomyces cerevisiae (O'Gorman et al 1991) and the CRE/lox system (Hoess et al 1982) from the bacteriophage P1)-might significantly reduce the selection and screening process.…”
Section: Introductionmentioning
confidence: 99%
“…It has been referred to as one of the main bottlenecks of getting a producer cell line out of development and into the manufacturing environment (Borth et al 2000;Carroll and Al-Rubeai 2004). A heterogeneous cell population that undergoes selection for high producers have the disadvantage that the high producing clones mainly have a reduced proliferation rate due to the energy being diverted towards production (Borth et al 2000;Cytotechnology (2007) 53:3-22 5 Kim and Lee 1999;Kromenaker and Srienc 1994). However, recently we found from genomics and metabolomics data that the increased specific recombinant protein productivity in arrested or slow growing cells is the result from overall increase in cell growth rather than from a diversion of cellular energy (unpublished data).…”
Section: Optimization Of Selection Proceduresmentioning
confidence: 99%
“…In terms of cell line productivity, studies have reported that copy number may not be a viable indicator for productivity and cell line stability rather that mRNA level can be more of a predictive indicator (Barnes et al 2003(Barnes et al , 2004. The location of the amplified genes also determines the stability since studies on CHO cells during prolonged culture showed that in the absence of selective agent such as Methotrexate (MTX), genes have higher stability when located in the telomeric regions of chromosomes (Kim and Lee 1999;Yoshikawa et al 2000). Recently research has shown that over-expression of human telomerase reverse transcriptase (hTERT), which adds hexameric repeats to the chromosome ends preventing telomeric loss, enhances chromosomal stability in CHO cell lines and possibly production stability (Crea and Al-Rubeai 2006).…”
Section: Stabilitymentioning
confidence: 99%